2017
DOI: 10.13102/sociobiology.v64i2.1386
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary list of the Ant Fauna in Northeastern Sahara of Algeria (Hymenoptera: Formicidae)

Abstract: We present here a preliminary list of ant fauna of some study sites in the northeastern Sahara of Algeria using two methodologies, quadrat and pitfall traps (Barber-pots) methods. This work was conducted in wild and agricultural ecosystems in the basin of Ouargla, El-Oued region and Djamaa region. We record a total of 26 species of 12 genera belonging to three subfamilies Dolichoderinae, Formicinae, and Myrmicinae. Species of the Myrmicinae and Formicinae were the most abundant with 62.96% and 29.63% respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Wetterer 2012Wetterer (2012) (Sarnat et al, 2015) Strumigenys membranifera Chemala et al (2017) ≤ 1904 (Forel, 1904) as Taheri et al (2017) Afrotropical in Aïn Moussa, Ouargla, S. membranifera santschii in Marrakesh (Wetterer, 2015) wild ecosystem…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wetterer 2012Wetterer (2012) (Sarnat et al, 2015) Strumigenys membranifera Chemala et al (2017) ≤ 1904 (Forel, 1904) as Taheri et al (2017) Afrotropical in Aïn Moussa, Ouargla, S. membranifera santschii in Marrakesh (Wetterer, 2015) wild ecosystem…”
Section: Resultsmentioning
confidence: 99%
“…According to Deyrup (1997), Strumigenys membranifera often occurs in disturbed open areas, such as lawns and pastures. A queen of this species was recently collected from the wild ecosystem of Ouargla region, Algeria (Chemala et al, 2017). Among the 873 dacetine species, only three species have achieved wide distributional ranges: S. rogeri Emery, 1890; S. emmae (Emery, 1890) and S. membranifera, see Bolton (1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in the northern part of the same park, precisely in the forests of Tizi Ouzou, Djioua and Sadoudi-Ali Ahmed (2015), Myrmicinae dominates with 57% at all stations. In another type of landscape, in the northeastern Sahara, Chemala et al (2017) reported the dominance of Myrmicinae (62 %). In Chott El Hodna, Barech et al (2016), four subfamilies (Dolichoderinae, Formicinae, Myrmicinae and Dorylinae) have been highlighted.…”
Section: Discussionmentioning
confidence: 97%
“…In Algeria, six sub-families have been reported: Formicinae, Myrmicinae, Dolichoderinae, Ponerinae, Dorylinae, and Proceratiinae (Cagniant, 1968(Cagniant, , 1970aDehina et al, 2013). Several authors have studied myrmecofauna in Algeria: Cagniant (1966Cagniant ( , 1968Cagniant ( , 1969Cagniant ( , 1970aCagniant ( , 1970bCagniant ( , 1973, Dehina et al (2013), Bouzekri et al (2014), Djioua and Sadoudi-Ali Ahmed (2015), Barrech et al (2016), and Chemala et al (2017).…”
Section: Introductionmentioning
confidence: 99%